(untitled) (Economics and region, 2023)
The concept of capital investment has been compared, as there are certain differences in the interpretation of this economic term between international financial reporting standards and domestic standards. Changes in capital investments caused by the COVID pandemic are considered. It is noted that the current trends in capital investment of chemical enterprises have undergone changes, namely reorientation to the needs of the market: the production of the sector of personal protective equipment and raw materials for them has increased, there has been a partial reorientation of work processes due to the introduction of new business models caused by the violation of logistical obligations; introduction of digital commerce through the active use of various Internet platforms. It was noted that the main directions of capital investments of chemical enterprises in sustainable development (investments in environmental, social and management projects) have gained additional importance and relevance. It is indicated that, first of all, chemical enterprises are ready to attract capital investments in order to increase the competitiveness of their products. It was concluded that chemical enterprises need to reconsider their intentions in investing capital, taking into account the risks of globalization and focusing on opportunities for the localization of chemical production within one region or country, because this will open up new opportunities for chemical enterprises to develop at the expense of expanding their national interests. The directions of capital investments proposed in the article allow timely diagnosis of economic risks caused by the pandemic and reduce critical consequences within the national chemical industry.